Magnetic resonance imaging in rabies encephalitis, a case report, and review of the literature - Abasin Tajmalzai, MD, MPH, PGD; Ataullah Zarabi, MD, MPH, PGD (Radiology Case Reports, 2024)
Rabies is an acute fatal disease of the central nervous system. Neuroimaging plays an important role, especially in establishing an early diagnosis and distinguishing it from other types of encephalitis. This case report aims to give a brief review of this condition and report the less common MRI findings of the disease. We herein report a case of a 61-year-old male bitten by a stray dog who presented with fever, vomiting, headache, sialorrhea, dysarthria, dysphagia, and upper limb weakness which progressed to lower limbs on the next day. T2W and FLAIR images demonstrated subtle bilateral hyperintense signal in the deep gray matter with more apparent increased signal intensity in the white matter of the frontal and parietal lobes which shows mild diffusion restriction but no postcontrast enhancement. The diagnosis of rabies encephalitis was made based on a typical history of exposure, a compatible clinical presentation, and MRI findings. Rabies diagnosis is essentially clinical. It is definitively confirmed by the isolation of the virus from biological samples such as saliva, CSF, hair, or detection of rabies antigens or antibodies. Magnetic resonance imaging (MRI) brain used as one of the modalities of investigation for distinguishing it from other encephalitis. Rabies per se does not have any characteristic features on the MRI brain.